Analysis of reproduction-related transcriptomes on pineal-hypothalamic-pituitary-ovarian tissues during estrus and anestrus in Tan sheep - Wei, Shihao; Kang, Xiaolong; Yang, Chaoyun; Wang, Feng; Dai, Tianshu; Guo, Xingru; Ma, Ziming; Li, Chenglong; Zhao, Hongxi; Dan, Xingang (Frontiers in Veterinary Science, 2022)
Seasonal estrus is an important factor limiting the fertility of some animals such as sheep. Promoting estrus in the anestrus season is one of the major ways in improving the fecundity of seasonally breeding animals. The pineal-hypothalamus-pituitary-ovary (PHPO) axis plays a decisive role in regulating animal reproduction. However, the molecular mechanisms by which the PHPO axis regulates seasonal reproduction in animals are not well understood, especially in Tan sheep. To this end, we collected pineal, hypothalamus, pituitary and ovary tissues from Tan sheep during estrus and anestrus for RNA-Sequencing, and performed bioinformatics analysis on the entire regulatory axis of the pineal-hypothalamic-pituitary-ovary (PHPO). The results showed that 940, 1638, 750 and 971 DEGs (differentially expressed genes, DEGs) were identified in pineal, hypothalamus, pituitary and ovary, respectively. GO analysis showed that DEGs from PHPO axis-related tissues were mainly enriched in "biological processes" such as transmembrane transport, peptide and amide biosynthesis and DNA synthesis. Meanwhile, KEGG enrichment analysis showed that the bile acid secretion pathway and the neuroactive ligand-receptor interaction pathway were significantly enriched. Additionally, four potential candidate genes related to seasonal reproduction (VEGFA, CDC20, ASPM and PLCG2) were identified by gene expression profiling and protein-protein interaction (PPI) analysis. These findings will contribute to be better understanding of seasonal reproduction regulation in Tan sheep and will serve as a useful reference for molecular breeding of high fertility Tan sheep.